Simultaneously Boosting the Mass and Fixed-carbon Yields of Charcoal from Forest Residue via Atmospheric Carbonization. (May 2017) - Tran, Khanh-Quang; Alonso, Maria Zabalo; Wang, Liang; Skreiberg, Øyvind
Abstract: The carbonization of various forest residues in comparison with their stem wood was studied by means of thermogravimetric analyzer operated non-isothermally at atmospheric pressure with a heating rate of 10K/min and a final temperature of 800 °C. GROT (tops and branches) and stem wood samples of Norway spruce and birch trees collected from forests in Southern Norway were used as feedstock. The work focused on analyzing the effect of process parameters (feedstock particle size, initial mass, and the residence time of gas released during the devolatilization) on the mass and fixed carbon yields of charcoal produced. The results show that it is possible to simultaneously improve the mass and fixed carbon yield of biochar produced by controlling the fate of gas released during devolatilization to promote the formation of secondary char. Differences between forest residues and theirs stem wood with regards to the effect of the investigated process parameters were observed.